Experimental study on uniaxial tensile and compressive behavior of high toughness cementitious composite (Fracture and Structural Integrity, 2017)
Though the principle of orthogonal experimental design, the uniaxial compression experiment and uniaxial tensile experiment were carried out on nine groups of high toughness cementitious composites with different mixing ratios to study the influence of four factors, namely fly ash content, water-binder ratio, sand-binder ratio and plasticizer content on the compressive strength and ultimate tensile strain of high toughness cementitious composites. The experiment results show that PVA fibers content greatly influenced the flexural behavior and the influence of the four factors on the compressive strength and ultimate tensile strain of high toughness cementitious composite is basically the same, the primary and secondary order is: water-binder ratio, fly ash content, plasticizer content and sand-binder ratio.
Keywords: High toughness cementitious composite; Orthogonal experiment design; Mixing ratio; Compressive strength; Ultimate tensile strain